#### Answer

$v \cdot j =12; a \cdot j =26$

#### Work Step by Step

$v=\dfrac{dx}{dt}i+\dfrac{dy}{dt}j$
$\implies v \cdot j=\dfrac{dy}{dt}=\dfrac{1}{3}x^2 \dfrac{dx}{dt}$
Since, $\dfrac{dx}{dt}=4$
$v \cdot j (3,3)=\dfrac{4}{3}x^2=\dfrac{4}{3}\times 3^2=12$
Now, $a(t)=\dfrac{2}{3}x(\dfrac{dx}{dt})^2+\dfrac{1}{3} x^2 \dfrac{d^2 x}{dt^2} $
So, $a \cdot j=\dfrac{2}{3}x(\dfrac{dx}{dt})^2+\dfrac{1}{3} x^2 \dfrac{d^2 x}{dt^2} =\dfrac{2}{3}x(4)^2+\dfrac{1}{3} (3)^2 (-2) =26$
So, $v \cdot j =12; a \cdot j =26$